A 1 MHz soft-switching boost DC-DC converter with matching network - Hur Jedi; Ghasan Ali Hussain (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper introduces a high-performance zero-voltage-switching (ZVS) boost converter, which is capable to operate under different load currents. By utilizing matching network, the proposed topology can achieve ZVS over a wide range of input voltages. Due to the switching loss is minimized, the proposed circuit is suitable for operation at switching frequencies on the order of several MHz. Steady-state analysis and detailed description of the proposed circuit are discussed. The power-loss and design procedure are introduced. The proposed converter has been simulated to verify the presented analytical approach at 1 MHz and deliver 80 W output. The peak power efficiency achieves 94.2%.